The Effect of Good Corporate Governance, Institutional Ownership, and Capital Structure on Corporate Financial Performance in Energy Sector Companies Listed on the Indonesia Stock Exchange - Pradhika Radya; Galuh Tresna Murti (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
The energy sector in Indonesia was one of the strategic sectors that contributed significantly to the national economy; however, the financial performance of companies in this sector tended to fluctuate due to external pressures such as changes in global commodity prices, declining export demand, and increasing operational costs. These conditions caused instability in corporate earnings and profitability, which created uncertainty for investors and other stakeholders. Financial performance served as an important indicator in assessing a company’s ability to manage its resources and sustain business continuity. Therefore, it was necessary to analyze internal corporate factors that were presumed to influence financial performance in a more controlled and sustainable manner. This study aimed to analyze the effect of Good Corporate Governance, Institutional Ownership, and Capital Structure on Corporate Financial Performance in energy sector companies listed on the Indonesia Stock Exchange. Good Corporate Governance was measured using the Corporate Governance Index, Institutional Ownership was measured by the proportion of shares owned by institutions to total outstanding shares, and Capital Structure was measured using the Debt to Equity Ratio (DER). Corporate Financial Performance was proxied by Return on Assets (ROA). This study examined both the simultaneous and partial effects of the independent variables on the dependent variable. This study used a quantitative approach with an associative research design. The population consisted of 91 energy sector companies listed on the Indonesia Stock Exchange. The sampling technique used non-probability sampling with a purposive sampling method based on predetermined criteria. The data were analyzed using panel data regression, with model selection conducted through the Chow Test, Hausman Test, and Lagrange Multiplier Test. Hypothesis testing was performed using the F-test, t-test, and the Coefficient of Determination (R²). The findings were expected to provide empirical evidence regarding the influence of corporate governance, ownership structure, and capital structure on the financial performance of energy sector companies.